AWS MasterClass : Storage & CDN : AWS S3 & AWS CloudFront - Aggarwal, Manuj (Packt Publishing, 2018)
"In this course, we will focus on implementing DevOps practices in the cloud using an aggregation of very potent tools and services. We will learn about AWS CodePipeline, AWS CodeDeploy and tie it all together with Jenkins. AWS CodePipeline and AWS CodeDeploy are DevOps focused services offered by Amazon Web Services. This combination of toolsets provides end-to-end capabilities of fully automating your source code builds, testing, and deployment. Implementing these tools and DevOps practices can help us immensely in reducing the risk within our software development lifecycle by catching bugs early and increasing the quality of our software products. This, in turn, reduces the overall cost of developing innovative software in any environment - startups and enterprise alike. When any startup or technology company is looking to implement DevOps practices to automate their infrastructure they are willing to pay handsomely for DevOps engineers and consultants to help them manage their infrastructure. Wouldn't you want to acquire these skills and be a part of this cloud computing revolution? Be highly sought after and take your career to the next level? Imagine getting that promotion in your current role. Imagine getting chased by recruiters looking for the skilled and experienced engineers that companies are desperately seeking to hire. Imagine getting a massive bump in your income as a result of your newly acquired in-demand skills. That's what we want for you, and we know it's what you want for yourself, so grab your copy of DevOps with AWS CodePipeline, Jenkins and AWS CodeDeploy now and let's get you started today!"--Resource description page